Molecular survey of hemoplasmas and Coxiella burnetii in vampire bats from northern Brazil - de Mello, Victória Valente Califre [UNESP]; de Oliveira, Laryssa Borges [UNESP]; Coelho, Taciana Fernandes Souza Barbosa; Lee, Daniel Antonio Braga [UNESP]; Franco, Eliz Oliveira [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2024)
In addition to zoonotic viral pathogens, bats can also harbor bacterial pathogens, including hemoplasmas (hemotropic mycoplasmas) and Coxiella burnetii. The present study aimed to investigate, using molecular techniques, the presence of hemoplasmas and C. burnetii in spleen samples from vampire bats in northern Brazil. For this purpose, between 2017 and 2019, spleen samples were collected from Desmodus rotundus (n = 228) and Diaemus youngii (n = 1) captured in the states of Pará (n = 207), Amazonas (n = 1), Roraima (n = 18) and Amapá (n = 3). DNA samples extracted from the bat spleen and positive in PCR for the endogenous gapdh gene were subjected to conventional PCR assays for the 16S rRNA, 23S rRNA and RNAse P genes from hemoplasmas and to qPCR based on the IS1111 gene element for C. burnetii. All spleen samples from vampire bats were negative in the qPCR for C. burnetii. Hemoplasmas were detected in 10 % (23/229) of spleen samples using a PCR based on the 16S rRNA gene. Of these, 21.73 % (5/23) were positive for the 23S rRNA gene and none for the RNAseP gene. The seven hemoplasma 16S rRNA sequences obtained were closely related to sequences previously identified in vampire bats from Belize, Peru and Brazil. The 23S rRNA sequence obtained revealed genetic proximity to hemoplasmas from non-hematophagous bats from Brazil and Belize. The analysis revealed different circulating genotypes among Brazilian vampire bats, in addition to a trend towards genera-specific hemoplasma genotypes. The present study contributes to the knowledge of the wide diversity of hemoplasmas in vampire bats.
Keywords: Genetic diversity; Hemoplasmas; Q fever; Vampire bats